Chapter Transitions in Art, Culture, and Politics: An Introduction - Ponzanesi, Sandra (Amsterdam University Press, 2023)
This volume focusses on the role of art, culture and politics in transitions and the struggle for social justice. Sometimes these transitions are traumatic and violent processes as in the case of post-apartheid South Africa. In other cases, as in Europe, they involve long-standing histories that are multi-directionally linked to colonialism, holocaust and totalitarianism. The authors explore intersectional issues of transition and social change in conjunction with broader debates on the role of democracy, citizenship and human rights. In doing so, they engage with the work of feminist scholar Rosemarie Buikema.